Occupancy of platelet receptors for platelet-activating factor in patients with septicemia. - Lopez Diez, F (1989)
The possible involvement of platelet-activating factor (PAF) in the pathogenesis of endotoxemia, was investigated by using a binding assay to patients' platelets, complemented with the extraction and chemical characterization of PAF obtained from patients' platelets. Platelets from 12 human volunteers had 281 +/- 63 freely accessible high affinity binding sites (PAF-receptors) per platelet; whereas this number was of 49 +/- 37 PAF-receptors per platelet, n = 14 samples, P less than 0.01, in a group of 13 patients with positive blood culture. A group of patients with respiratory or cardiovascular disturbances and negative blood culture had 253 +/- 74, accessible receptors per platelet (n = 19 samples from 16 patients, P less than 0.01 as compared to septic patients, which was not significantly different when compared to control individuals). Patients with sepsis possessed significant amounts of PAF associated to their platelets, whereas this mediator could not be isolated from platelets of patients with respiratory or cardiovascular disturbances and negative blood culture, nor from platelets of control individuals. PAF was also assayed in whole blood samples and found at high concentrations in sepsis patients. These data indicate that occupancy of PAF receptors in combination with high amounts of platelet-associated PAF, is a common finding in patients with sepsis.